Новый вид-двойник среди полужесткокрылых, обнаруженный по личиночной фазе в роде Physatocheila Fiеb. (Heteroptera, Tingidae) - Пучков, В.Г. (Вестник зоологии, 1969)
The literary data on the species Ph. costata F. and Ph. smreczynskii C h і n a of Physatochella genus are compared as well as the peculiarities in the structure of this genus larva, gathered from Alnus, Malus, Prunus and Sorbus. It is established, that two species were hidden under the title Ph. smreczynskii China, 1952. Their difference in adult form is not established, but it is quite clear in larvae form. New species, Physatocheila forsteri Putshkov sp. n. is described on the larva of the Vth stage and differs well from the other representatives of the species in absence of the thorns on the lateral margins of the wing pads and abodomen (only the dorsal angles of the IX segment of the abdomen are protruded into the thick processes with adjoining tops). The thorns along the middle of the abdomen are short tightly pressed to the body. It lives on Sorbus aucuparia and is found in the Ukrainian SSR and German Federal Republic.The literary data on the species Ph. costata F. and Ph. smreczynskii C h і n a of Physatochella genus are compared as well as the peculiarities in the structure of this genus larva, gathered from Alnus, Malus, Prunus and Sorbus. It is established, that two species were hidden under the title Ph. smreczynskii China, 1952. Their difference in adult form is not established, but it is quite clear in larvae form. New species, Physatocheila forsteri Putshkov sp. n. is described on the larva of the Vth stage and differs well from the other representatives of the species in absence of the thorns on the lateral margins of the wing pads and abodomen (only the dorsal angles of the IX segment of the abdomen are protruded into the thick processes with adjoining tops). The thorns along the middle of the abdomen are short tightly pressed to the body. It lives on Sorbus aucuparia and is found in the Ukrainian SSR and German Federal Republic.